Thromboembolism and bleeding in systemic amyloidosis: a review. (16th November 2021) - Nicol, Martin; Siguret, Virginie; Vergaro, Giuseppe; Aimo, Alberto; Emdin, Michele; Dillinger, Jean Guillaume; Baudet, Mathilde; Cohen‐Solal, Alain; Villesuzanne, Camille; Harel, Stephanie; Royer, Bruno; Arnulf, Bertrand; et al.
Abstract: The assessment of both thromboembolic and haemorrhagic risks and their management in systemic amyloidosis have been poorly emphasized so far. This narrative review summarizes main evidence from literature with clinical perspective. The rate of thromboembolic events is as high as 5–10% amyloidosis patients, at least in patients with cardiac involvement, with deleterious impact on prognosis. The most known pro‐thrombotic factors are heart failure, atrial fibrillation, and atrial myopathy. Atrial fibrillation could occur in 20% to 75% of systemic amyloidosis patients. Cardiac thrombi are frequently observed in patients, particularly in immunoglobulin light chains (AL) amyloidosis, up to 30%, and it is advised to look for them systematically before cardioversion. In AL amyloidosis, nephrotic syndrome and the use of immunomodulatory drugs also favour thrombosis. On the other hand, the bleeding risk increases because of frequent amyloid digestive involvement as well as factor X deficiency, renal failure, and increased risk of dysautonomia‐related fall.